Salt water neighbors :international ocean law relations between the United States and Canada - McDorman, Ted L. (New York ; Oxford : Oxford University Press, 2009)
This title examines both the international ocean law disagreements that exist between the United States and Canada respecting maritime boundaries, fisheries and navigation rights and the numerous cooperative bilateral arrangements that have prevented these disputes from being significant causes of friction.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Territorial waters -- United States; Territorial waters -- Canada; Economic zones (Law of the sea); United States -- Boundaries -- Canada; Canada -- Boundaries -- United States